Level of Customer Satisfaction Towards Marketing Mix In Indonesian Traditional Market - ratih dwi kartikasari; Irham Irham; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
The competition of various shopping centers in attracting consumers is getting more intense due to the increased consumer purchasing power. Many studies show that consumers are more interested to shop in a modern market, which has many attractive facilities, but only a few studies have examined the satisfaction of consumers shopping in traditional markets. The purpose of this study was to examine the level of customer satisfaction in traditional markets and to find out the priority strategies for improving traditional market performance. The data was analyzed using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Non-probability sampling was employed with an accidental sampling technique to as many as 180 customers in 8 traditional markets in Indonesia. Based on the research analysis, the CSI value obtained was 74.25%, showing that the customers were satisfied with the performance of traditional market merchants. The most considered marketing mix attribute to consumers in shopping was the friendliness of merchants when serving their consumers. This means that consumers did not only pay attention to the type of products purchased but also consider the services they received in the transaction. The priority strategy that needs to be done is to maintain the performance of attributes in Concentrate Here quadrant which consist of product availability, market hygiene, product price in line with expectations, lower product price, additional free product for certain quantity purchase, and discounted price from merchants.